Rubber-clay nanocomposites science, technology, and applications - Galimberti, Maurizio (John Wiley & Sons, 2011)
"This book comprehensively reviews rubber-clay nanocomposites in a handbook format for R&D professionals. Along with valuable details on synthesis, processing, and mechanics, the book includes applications of rubber-clay nanocomposites in automotive tires and as polymer fillers. In addition, it helps scientists understand processing methods for nanocomposites preparation and nanostructure characterization. This book helps promote common knowledge and interpretation of the important aspects of rubber-clay nanocomposites, clarifying the main results achieved in the field of rubbers and crosslinked rubbers - not covered by the more general books on polymer-clay nanocomposites"--